Combating Digital Defamation: Regulations, Challenges and Protecting Reputation - Anis Mashdurohatun; Sugihartono, Bambang; Nurul Masrifah; Arief Indra Kusuma Adhi; Henning Glaser (Lembaga Contrarius Indonesia, 2025)
Indonesia regulates digital defamation through the ITE Law; however, the existing framework remains inadequate because it fails to achieve a balanced integration of reputation protection, freedom of expression, legal coherence, institutional coordination, and public awareness. This research aims to analyze regulatory inadequacies on digital defamation, identify weaknesses in the existing framework, and propose a justice-based reconstruction for Indonesia’s legal system. Employing a constructivist paradigm, this study adopts a socio-legal research approach with a descriptive type of analysis. Data were derived from secondary sources, including primary, secondary, and tertiary legal materials, collected through library research and analyzed qualitatively. The research demonstrates that Indonesia’s regulation of digital defamation remains unjust because it fails to adequately protect citizens’ right to express opinions without surveillance, restriction, or silencing. Substantively, lawmakers must critically reconsider Article 45 paragraph (4) of the ITE Law to ensure fair and consistent enforcement. Structurally, law enforcement institutions must strengthen coordination between the police, prosecutors, and judiciary to address weak institutional synergy. Culturally, policymakers and stakeholders must expand public dissemination of the ITE Law to improve legal understanding across society. Based on these findings, the study concludes that reconstructing the regulation of digital defamation requires embedding justice-oriented values into both legal norms and enforcement mechanisms, particularly through reforming Article 27A and Article 45 paragraph (5) of the ITE Law.